Does e-WOM and Product Quality Impact Purchase Decision in Tiktok Indonesia? - Romanisti, Shemma Anggia; Juniwati; Pebrianti, Wenny; Heriyadi; Jaya, Arman (Yayasan Ilomata, 2024)
The impact of this is that sales of beauty products can contribute significantly to a country's economy. Successful cosmetics companies can create jobs, pay taxes and contribute to economic growth. This can influence consumer preferences and provide companies with information about what the market is interested in. This study aims to determine the effect of electronic word of mouth and product quality on purchasing decisions mediated by brand image on Maybelline mascara products in Indonesia. The population in this study are people who have bought Maybelline mascara on TikTok social media at least twice. This study will use a causal design approach with Structural Equation Modeling (SEM) as a statistical approach to test constructs and hypotheses built with AMOS 24 statistical aids. The number of samples used in this study were 215 respondents who had bought Maybelline mascara on TikTok at least 2 times. The results of this study indicate that electronic word of mouth and product quality have a positive and significant effect on purchasing decisions mediated by brand image.